Acceptability of and barriers to human papillomavirus vaccination in China: A systematic review of the Chinese and English scientific literature. (1st March 2022) - Wang, Du; Wu, Jing; Du, Jianshu; Ong, Haley; Tang, Biwei; Dozier, Marshall; Weller, David; Campbell, Christine
Abstract: Introduction: Widespread adoption of the human papillomavirus (HPV) vaccine will require population acceptance and tailoring of immunisation services to community needs and preferences. We examined peer‐reviewed publications on the acceptability of and barriers to the HPV vaccine across China. Methods: We searched English (MEDLINE, Embase, and Web of Science) and Chinese (CNKI, VIP, Wanfang data) databases between 1 January 2006 and 31 December 2017. We adopted a narrative approach for data synthesis. Results: We identified 73 studies. The overall median acceptability of HPV vaccine was 71.8% (Q1–Q3: 58.6%–81%). Low levels of acceptability (<40%) of HPV vaccine were found in eastern regions of China. The largest differences of acceptability were observed between rural western regions (all >90%) and urban eastern regions (all <35%). Despite these regional variations, common barriers to HPV vaccine acceptance were concerns about vaccine safety, uncertainty over vaccine effectiveness, low perceived risk of cervical cancer and the price of the vaccine. The level of willingness to pay for the HPV vaccine (over 153 US dollars) was very low (<7%). Conclusion: The acceptability of and attitudes towards HPV vaccine vary by regions and populations across China. HPV vaccination programmes will need to tailor service delivery as well as information materials to take account of regional concerns.